1990
DOI: 10.1007/bf00018557
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a rice actin gene

Abstract: We have isolated and sequenced a full-length cDNA clone containing information for the rice actin gene RAc1. Transcript terminus mapping and sequence alignment between the RAc1 cDNA clone and a previously isolated RAc1 genomic clone were used to determine the structure of the RAc1 gene. This allowed us to make the first complete structural characterization of a plant actin gene. The analysis revealed the presence of a 5'-noncoding exon, separated by an intron, from the first translated exon of the RAc1 gene. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 27 publications
(51 reference statements)
4
46
0
Order By: Relevance
“…The sequence around the Actl transcription initiation site, as previously determined by primer extension analysis (McElroy et al, 1990), CCTACCA, is similar to the consensus sequences for transcription initiation, YYYAYYA (Y = pyrimidine), previously determined for a number of plant genes (Joshi, 1987). The 79-bp noncoding exon located 3' of the putative Actl TATA box is GC-rich (77.5%) and consists of a number of tandemly repeated TCC triplets (Figure 2, region vi).…”
Section: Characterization Of a Clone Containing The Rice Actl 5' Regionsupporting
confidence: 72%
See 3 more Smart Citations
“…The sequence around the Actl transcription initiation site, as previously determined by primer extension analysis (McElroy et al, 1990), CCTACCA, is similar to the consensus sequences for transcription initiation, YYYAYYA (Y = pyrimidine), previously determined for a number of plant genes (Joshi, 1987). The 79-bp noncoding exon located 3' of the putative Actl TATA box is GC-rich (77.5%) and consists of a number of tandemly repeated TCC triplets (Figure 2, region vi).…”
Section: Characterization Of a Clone Containing The Rice Actl 5' Regionsupporting
confidence: 72%
“…The resulting restriction map of the 15.1 -kb M c t l insert, together with an indication of the position of the Actl coding and noncoding exons (McElroy et al, 1990), is shown in Figure 1A. A 5.3-kb Hindlll fragment from the M c t l insert, spanning a region from 3.9 kb upstream of the Actl coding sequence to a point within its third coding exon, was isolated and cloned into the Hindlll site of pBluescriptll-KS (Stratagene) to produce the plasmid pActl-A.…”
Section: Characterization Of a Clone Containing The Rice Actl 5' Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmid pcRAc1.3 contains a 1.4-kb rice actin 1 cDNA insert in pBluescript II-KS (McElroy et al, 1990). Plasmid pRY18 carries a 3.8-kb DNA fragment that contains a rice genomic rDNA cluster, including the 3Ј-half portion of 18S rRNA gene, the complete 5.8S rRNA gene, and the 5Ј-half portion of the 25S rRNA gene in pUC13 (Sano and Sano, 1990).…”
Section: Plasmidsmentioning
confidence: 99%